Kemurungan dan Harga Diri di Kalangan Murid-Murid 'Latchkey' di Sekolah Kebangsaan di Pantai Timur Semenanjung - Yusoff, Emi Yusmidar Md; Mahamood, Yahaya (Faculty of Psychology, Universitas Surabaya, 2005)
The relation between depression and self-esteem among average students reveals a negative correlation, though environmental factors are sometimes taken into account. This study examined children with rather